2020
DOI: 10.1352/1944-7558-125.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Object Play to Young Children With Disabilities: A Systematic Review of Methods and Rigor

Abstract: In this systematic review, we examined the rigor and outcomes across 27 object play intervention studies using single-case research methodology. We focused on studies including children age 5 years or younger and examined several descriptive characteristics including materials, instructional packages, and settings. We also analyzed the facilitation and measurement of generalized play and several methodological features including quality, rigor, and visual analysis procedures. Overall, the identified studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Researchers might ask questions related to the two important differences between this study and Frey and Kaise’s (2011) study, which were the dosage of play expansions received by target children (i.e., children in this study received fewer play expansions) and the implementers (i.e., teachers versus researchers). Furthermore, previous research has shown systematic prompting is related to increases in child play complexity (Barton, 2015; Barton, Choi, & Mauldin, 2019; Barton, Gossett, et al, 2019; Barton, Murray, et al, 2019), which should be considered when planning play interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers might ask questions related to the two important differences between this study and Frey and Kaise’s (2011) study, which were the dosage of play expansions received by target children (i.e., children in this study received fewer play expansions) and the implementers (i.e., teachers versus researchers). Furthermore, previous research has shown systematic prompting is related to increases in child play complexity (Barton, 2015; Barton, Choi, & Mauldin, 2019; Barton, Gossett, et al, 2019; Barton, Murray, et al, 2019), which should be considered when planning play interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There is a burgeoning body of research focused on systematic play instruction for young children with disabilities (Barton, Murray, et al, 2019). This literature demonstrates that systematic prompting and differential reinforcement are related to increased frequency and diversity of play behaviors in young children (Barton, Choi, & Mauldin, 2019; Barton, Gossett, et al, 2019).…”
Section: Play Expansionsmentioning
confidence: 99%
“…Given well-described search and screening procedures (like those described by NAC, 2015; Steinbrenner et al, 2020), two additional factors should be considered when synthesizing evidence for a specific practice. First, gray literature should be included to the extent possible; these types of sources were excluded in the NAC (2015) and Steinbrenner et al (2020) reviews (and are also commonly excluded in small-scale reviews; for example, Barton et al, 2020; Severini et al, 2018). For the purposes of identifying evidence-based practices, gray literature generally includes descriptions of studies that are not published in peer-reviewed journals (Cooper et al, 2019).…”
Section: Potential Problems With Current and Widely Used Taxonomiesmentioning
confidence: 99%
“…As Barton, Murray, O’Flaherty, Sweeney and Gossett (2020) suggest, although the play is described as ‘internally driven’, most children are actually taught to play. This type of ‘non‐directed’ play occurs in high‐quality early childhood settings where children are provided with peer models and responsive teaching practices.…”
Section: Introductionmentioning
confidence: 99%
“…Barton et al., (2020) conducted a systematic review of the literature focussed on teaching early toy‐play skills to young children with developmental disabilities. Findings of this review described several interventions shown to be effective in teaching early play skills.…”
Section: Introductionmentioning
confidence: 99%